Social media use for occupational lung disease. Issue 2 (April 2017) - Harber, Philip; Leroy, Gondy
Abstract : Purpose of review: Social media have great impact on all aspects of life throughout the world. The utilization of social media for occupational lung disease, however, has been much more limited. This article summarizes recent literature concerning social media for occupational lung disease and identifies areas for additional use. Recent findings: Social media are used in six relevant areas: information dissemination, peer-to-peer communication, survey research data collection, participatory research and exposome data acquisition, assessing public concerns, and knowledge generation. There are very clear advantages for information dissemination from experts to workers and on a peer-to-peer basis, although variable credibility and accuracy concerns persist. For research, social media have been used for acquiring data posted for nonresearch purposes and for efficiently collecting information specifically for research. The benefits of efficiency, democracy, and very large data sources may counterbalance concerns about inadequate specification of recruitment strategies and limited control over data quality. Summary: The potential benefits of using social media for lung health–workplace interactions are much greater than the very limited current utilization.